Teaching technologies used in Education in the COVID-19 pandemic: an integrative review (Research, Society and Development, 2021)
The coronavirus pandemic (COVID – 19) caused the on-campus teaching to be paralyzed, causing an immediate change in the educational process worldwide. The aim of this study is to analyze through an integrative review the use of the various technologies applied in teaching in different areas of knowledge, during the COVID-19 pandemic. The research is of a qualitative nature on the relationship and application of technologies in / for teaching. According to the objective, it has a descriptive and exploratory character, using as technical procedures an integrative review in relation to the theme addressed. The research was carried out through articles indexed in the electronic databases in Science Direct and Google Scholar, published in Portuguese and English, from 2010 to 2020, considering the following descriptors: Technologies; Education; Pandemia and COVID-19. Inclusion criteria were consistency with the theme, and exclusion was repetition of articles or non-adequacy to the theme. 56 articles (n = 56) were found, which were reduced to (n = 12) after analysis. The data report that the inclusion of technologies, especially the digital ones incorporated by means of platforms for remote education, enables a better qualification in teaching, in addition to facilitating the learning of the developed contents.